Oral Immunization of Recombinant Lactococcus lactis and Enterococcus faecalis Expressing Dendritic Cell Targeting Peptide and Hexon Protein of Fowl Adenovirus 4 Induces Protective Immunity Against Homologous Infection - Jia, Zhipeng; Ma, Chunli; Yang, Xuelian; Pan, Xinghui; Li, Guangxing; Ma, Dexing (Frontiers in Veterinary Science, 2021)
Hepatitis-hydropericardium syndrome (HPS) causes severe economic losses in the global poultry industry. The present study aims to explore oral immunization of recombinant Lactococcus lactis and Enterococcus faecalis expressing Hexon protein of fowl adenovirus 4 (FAdV-4). The bacteria L. lactis NZ9000 and E. faecalis MDXEF-1 were respectively modified as host strain to deliver truncated Hexon protein (ΔHexon) or ΔHexon protein fusing with dendritic cell (DC) targeting peptide (DC-ΔHexon) on the surface of bacteria. The expression of target protein in L. lactis NZ9000 and E. faecalis MDXEF-1 were detected by western blot. To evaluate the immune responses and protective efficacies provided by the live recombinant bacteria, chickens were immunized with the constructed ΔHexon-expressing bacteria three times at two-week intervals, then experimentally challenged with hypervirulent FAdV-4/GX01. The results showed that oral immunizations with the four ΔHexon-expressing bacteria (NZ9000/ΔHexon-CWA, NZ9000/DC-ΔHexon-CWA, MDXEF-1/ΔHexon-CWA, and MDXEF-1/DC-ΔHexon-CWA), especially the two bacteria carrying DC-targeting peptide, stimulated higher levels of ΔHexon-specific sera IgG and secretory IgA (sIgA) in jejunal lavage fluid, higher proliferation of peripheral blood lymphocytes (PBLs) and higher levels of Th1/Th2-type cytokines, along with significantly decreased virus loads in liver and more offered protective efficacies against FAdV infection compared with PBS and empty vector control groups (p <0.01). For chickens in the group MDXEF-1/DC-ΔHexon-CWA, the levels of aspartate transaminase (AST), alanine transaminase (ALT) and lactate dehydrogenase (LDH) in sera, and the virus loads in livers were significantly decreased versus the other three ΔHexon-expressing bacteria (p <0.01). The pathological changes in the hearts, livers, spleens and kidneys of chickens in MDXEF-1/DC-ΔHexon-CWA group were relatively slight compared to infection control group and other three ΔHexon-expressing bacteria groups. The rate of protection in MDXEF-1/DC-ΔHexon-CWA group was 90%. The present work demonstrated that cell surface-displayed target protein and immune enhancers in L. lactis and E. faecalis might be a promising approach to enhance immunity and immune efficacy against pathogen FAdV-4 infection.